CONVERSÃO E JUSTIÇA SOCIAL EM JOSÉ COMBLIN - Cappelletti, Paulo (2012)
In the present study on the topic Concept of Conversion and Social Justice in the thoughts of Joseph Comblin I attempted to develop the concept of the theme proposed above. This thesis, developed in the Graduate Program in Science of Religion belongs to the Religion, Society and Culture line of research. The methodology for data collection was a bibliographical research. The question that guided the research was: what is the concept of conversion and social justice in the thought of Joseph Comblin? With the responses we developed the first chapter with Joseph Julles Comblin's biography along with people who somehow inspired and influenced his career in Brazil and in Latin America. In the second chapter Comblin's concept of conversion was presented; coming to a conclusion that a conversion is for the Kingdom of God and not for any religions institution. In the third chapter the concept of Social Justice was presented; coming to a conclusion that social justice happens when society becomes homeless with a practical love and not just words.